Production of Gluten–Free Breakfast Cereals Based on Red Rice by Extrusion Process (Indian Journal of Food Engineering (IJFE), 2024)
Ready-to-eat breakfast cereals (RTE-BC) is either extruded product from flour (or) flaked corn, wheat (or) rice commonly used as breakfast in western countries. Cereal fortification helps to eliminate many nutritional deficiencies in various developed nations including United States. Recent techniques used to make bio-available vitamins and minerals in breakfast cereals to overcome the nutritional deficiencies such as iron, calcium etc. The main objective of this study was development of readt to eat foods from cereals for breakfast using extrusion. Trial no.6 because of its Good consistency and sensory properties. Among all other trials the red rice and quinoa 42% is found to be effective in nutritional facts and consistency. Typically, breakfast cereals include flaked, puffed, shredded, granula, extrude and baked product Oryzapunctata (red rice) and Chenopodium quinoa (quinoa seed), two gluten free food grains help to replace the wheat which contains gluten and used for the production of breakfast cereals. Quinoa is good example for the functional food that aims to lower the risk of various debilitating diseases and identify the presence of phyto-hormones of as several advantages for human nutrition over other plant foods. The Orzyapunctata (red rice) with high antioxidant content can be supplemented in the form of breakfast cereal so as to reduce the usage of artificial antioxidant BHT (butylated hydroxyl toluene).